Buckling restrained braced frames as a seismic force resisting system - Fuqua, Brandon W. (Kansas State University, 2009)
The hazards of seismic activity on building structures require that engineers continually look for new and better methods of resisting seismic forces. Buckling restrained braced frames (BRBF) are a relatively new lateral force resisting system developed to resist highly unpredictable seismic forces in a very predictable way. Generally, structures with a more ductile lateral force resisting system perform better in resisting high seismic forces than systems with more rigid, brittle elements. The BRBF is a more ductile frame choice than special concentrically braced frames (SCBF). The ductility is gained through brace yielding in both compression and tension. The balanced hysteretic curve this produces provides consistent brace behavior under extreme seismic loads. However regular use of the BRB is largely limited to Japan where the brace type was first designed. The wide acceptance of buckling restrained braced frames requires the system to become easily designable, perform predictably, and common to engineers. This report explains the design process to help increase knowledge of the design and background. This report also details a comparison of a BRBF to a SCBF to give familiarity and promote confidence in the system. The design process of the BRBF is described in detail with design calculations of an example frame. The design process is from the AISC Seismic Provisions with the seismic loads calculated according to ASCE 7 equivalent lateral force procedure. The final members sizes of the BRBF and SCBF are compared based on forces and members selected. The results of the parametric study are discussed in detail.
Keywords: Buckling Restrained Braced Frame; Special Concentrically Braced Frame; Seismic; Lateral Force Resisting System; BRBF; SCBF; Engineering, Civil (0543); Engineering, General (0537)